CAR T Cell Therapy of Non-hematopoietic Malignancies: Detours on the Road to Clinical Success - Long, Kristen B.; Young, Regina M.; Boesteanu, Alina C.; Davis, Megan M.; Melenhorst, J. Joseph; Lacey, Simon F.; DeGaramo, David A.; Levine, Bruce L.; Fraietta, Joseph A. (Frontiers in Immunology, 2018)
Chimeric antigen receptor (CAR)-engineered T cells represent a breakthrough in personalized medicine. In this strategy, a patient’s own T lymphocytes are genetically reprogrammed to encode a synthetic receptor that binds a tumor antigen, allowing T cells to recognize and kill antigen-expressing cancer cells. As a result of complete and durable responses in individuals who are refractory to standard of care therapy, CAR T cells directed against the CD19 protein have been granted FDA approval as a therapy for treatment of pediatric and young adult acute lymphoblastic leukemia and diffuse large B cell lymphoma. Human trials of CAR T cells targeting CD19 or B cell maturation antigen in multiple myeloma have also reported early successes. However, a clear and consistently reproducible demonstration of clinical efficacy of CAR T cells in the setting of solid tumors has not been reported to date. Here, we review the history and status of CAR T cell therapy for solid tumors, potential T cell-intrinsic determinants of response and resistance as well as extrinsic obstacles to the success of this approach for much more prevalent non-hematopoietic malignancies. In addition, we summarize recent strategies and innovations that aim to augment the potency of CAR T cells in the face of multiple immunosuppressive barriers operative within the solid tumor microenvironment. Advances in the field of CAR T cell biology over the coming years in the areas of safety, reliability, and efficacy against non-hematopoietic cancers will ultimately determine how transformative adoptive cell therapy will be in the broader battle against cancer.